Re-assessing the fodder problem - Dhamankar, M. (2010)
Small-scale farmers depend largely on their animals and need to feed them well. Technology based innovations have been the mainstream solution to improve the fodder problem. But making farmers find relevant information and networks appears to be as much effective for innovation.